Toughness Enhancement of Stereocomplexed Polylactide for Use as Microwavable Packaging Materials - Sunan Tacha (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Stereocomplexed polylactide (Sc-PL) is known to demonstrate good heat distortion due to its relatively high melting temperature. However, its brittle characteristic has been a major drawback of Sc-PL, which limits its use to certain applications. This project is aimed to improve the toughness of Sc-PL. So, poly(D-lactide) (PDL) and PDL-poly(ethylene glycol)-PDL (PDL-PEG-PDL) copolymers (PEG molecular weight 8,000) were synthesized by ring-opening polymerization using stannous octoate as an initiator. Each of the synthesized PDL homopolymer and PDL-PEG-PDL copolymers were blended with a commercially available poly(L-lactide) (PLL) to prepare stereocomplexedpolylactide (Sc-PL). Blending methods included solution-blending and melt-blending, by which final Sc-PL specimens were achieved as Sc-PL films and Sc-PL sheets, respectively. The Sc-PL sheets were further proceeded to make tray packaging by thermoforming method. The DSC thermograms of the Sc-PL films showed that completed Sc-crystallites were formed when at least 40% copolymers were blended in the films. Sc-crystallinity increased with increasing PDL block length in the copolymer. AFM phase imaged showed that the size of Sc-crystallites was increased with increasing PDL block length in the copolymer, which showed a great effect on enhancing stress at break of the Sc-PL films. In addition, elongation at break of the Sc-PL films showed good correlation with percentage amorphous area determined by AFM phase analysis. So, the morphology-property relationship of the Sc-PL films was established, which showed that the toughness of the Sc-PL films was greatly influenced by the balance between the Sc-crytalline size and the percentage amorphous area of the system. For melt blending, Sc-PL sheets from PLL and copolymer were successfully prepared in certain compositions and the thermoformed tray was only achieved for 90/10 wt% of PLL/copolymer Sc-PL sheet. Toughness of the PLL/copolymer Sc-PL sheet, measured by impact testing method, was found to be slightly higher than that of the commercial PLL sheet. Mechanical properties of Sc-PL after being microwave-heated were also examined. The result indicated that the PLL/PDL-PEG-PDL Sc-PL film can be used in a microwave oven that operates with the power up to 600 Watts. On the other hand, a deformation of the whole shape was observed for the tray prepared from the commercial PLL sheet. Also, the tray packaging prepared from PLL/copolymer blended sheet showed that the try started to melt from the bottom.